Cover page, CONTENTS (Discussion Papers, 2012)
The present document was prepared in the framework of the Carpathian Project. The Car-pathian Project, again, is one of the projects approved and prepared in the frame¬work of the CADSES (Central European, Adriatic, Danubian and South¬east Euro¬pean Space) trans-national spatial planning cooperation programme. VASICA is accordingly a trans-national spatial-planning document. The document is dealing first of all with the specific problems of the Carpathian countries and above all with those of the mountainous areas of the region. It means that in order to imple-ment a success¬ful spatial planning and policy in the Carpathian area, one should keep in mind not only specific proposals and recommendations (contained in VASICA), but the general principles and guidelines contained in European documents as well. The VASICA document is a conceptual document based on a social-economic analysis, which is ex¬ploring some development opportunities in the Carpathian area and sets some priorities for development actions. It has 13 chapters: 1. Introduction, 2. The Carpathians in the European space, 3.Brief review of the situation and SWOT analysis, 4. Strate¬gic objectives, 5. Demography, 6. Agriculture and Forestry, 7. Mining and Manu¬facturing, 8. Urban Network, 9. Cultural and Natural Heritage, 10.Transport, 11. Environment, 12. Tourism, 13. European Territorial Coopera¬tion. With the excep¬tion of the first five, all chapters consist of two parts: the first part is the presenta¬tion of the problems; the second part contains the policy recommendations and proposals for actions. During the preparation of VASICA the GIS databases and appropriate tech¬nologies were used to provide VASICA with maps and other cartographical mate¬rials, which were published on the Carpathian Geoportal. Interactive maps of devel¬opment issues for the entire Carpathian transnational region (at a scale of 1:2,000,000) have been prepared jointly for the whole area. The document takes into account the joint development potentials for cross border areas. VASICA should help coordinate actions, especially those regarding cross-border areas. Benefits are also expected in the form of intensified interna¬tional cooperation at multilateral and bilateral levels.